LINEAR AND VOLUMETRIC METHODS OF PRESENTATION OF THE TEACHING INFORMATION - Merzliakova, Olena L. (Educological discourse, 2016)
The article acquaints with features of linear and volumetric (visual, graphic) methods of information representation. It is shown advantages and shortcomings of each of the presented ways of a statement of information. The author shows an urgent need of more active use of visual forms of information representation by a teacher that is caused by sharp expansion of modern information space of knowledge. The use by teachers of modern methods of work with information massifs accompanies their general development of information literacy. Possibilities of use of a volumetric way of information representation in everyday teaching practice are offered. Visualization of information massifs of knowledge will promote for growth of information literacy of the teacher that is the perspective direction of further researches.